2005
DOI: 10.1016/j.cub.2005.05.059
|View full text |Cite
|
Sign up to set email alerts
|

The Zinc Finger of the CSN-Associated Deubiquitinating Enzyme USP15 Is Essential to Rescue the E3 Ligase Rbx1

Abstract: The COP9 signalosome (CSN) is a conserved protein complex found in all eukaryotic cells and involved in the regulation of the ubiquitin (Ub)/26S proteasome system. It binds numerous proteins, including the Ub E3 ligases and the deubiquitinating enzyme Ubp12p, the S. pombe ortholog of human USP15. We found that USP15 copurified with the human CSN complex. Isolated CSN complex exhibited protease activity that deubiquitinated poly-Ub substrates and was completely inhibited by o-phenanthroline (OPT), a metal-chela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
163
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(169 citation statements)
references
References 23 publications
6
163
0
Order By: Relevance
“…Migrations of complexes that cross-react with the anti-CSN6 antibody were not affected by apoptosis. This was also true for the associated enzyme USP15, which co-sedimented with the CSN into fraction 8 (data not shown) and partially dissociated during glycerol gradient centrifugation as published before [31]. As seen in Fig.…”
Section: Caspase Cleavage Of Csn6 Is Accompanied By Cleavage Of Rbx1supporting
confidence: 80%
See 2 more Smart Citations
“…Migrations of complexes that cross-react with the anti-CSN6 antibody were not affected by apoptosis. This was also true for the associated enzyme USP15, which co-sedimented with the CSN into fraction 8 (data not shown) and partially dissociated during glycerol gradient centrifugation as published before [31]. As seen in Fig.…”
Section: Caspase Cleavage Of Csn6 Is Accompanied By Cleavage Of Rbx1supporting
confidence: 80%
“…Aliquots were subjected to SDS-PAGE and Western blotting. The following antibodies were used in this study: anti-CSN1, anti-CSN4, anti-CSN6 and anti-CSN8 antibodies (Biomol), anti-CSN2, anti-CSN3 and anti-CSN7 antibodies [29,30], monoclonal anti-CSN5 antibody (supplied by B. Christy), anti-ubiquitin antibody (FK2, Biomol), anti-USP15 antibody [31], anti-Rbx1 antibody (Rockland), anti-Nedd8 antibody (a gift from C.…”
Section: Cell Culture and Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies from a range of organisms have shown that CSN interacts with Cullin-RING E3s and that proper E3 function is dependent on CSN and more specifically on CSN5-mediated deneddylation Schwechheimer et al, 2001;Schwechheimer, 2004). Some recent studies suggest that deneddylation is required for E3 subunit stability or E3 complex assembly (Hetfeld et al, 2005;Wee et al, 2005;Wu et al, 2005;Bornstein et al, 2006). Furthermore, it has been proposed that CSN is part of a proteasome-related complex (Peng et al, 2001(Peng et al, , 2003.…”
Section: Introductionmentioning
confidence: 99%
“…In the subsequent years, the highly conserved protein complex was also found in fungi (3,4), Caenorhabditis elegans (5), Drosophila melanogaster (6), and mammals (7,8). The most studied function of the CSN complex in eukaryotes is the regulation of protein degradation through two pathways, deneddylation (9)(10)(11) and deubiquitination (12,13). In the deneddylation pathway, the CSN complex can influence the cullin-RING ligase activity by removing Nedd8, a ubiquitin-like protein, from a cullin (9,14).…”
mentioning
confidence: 99%